(untitled) (Revista Brasileira Multidisciplinar, 2023)
Research on snakes has a wide range of studies given the great diversity of extinct and living specimens, raising numerous questions about the emergence, development and evolutionary success of these animals. Thus, the main objective of this work is to presentan overview of the originan devolution of Boid saccording to diferente hypotheses, as well as to identify and reporten vironmental factors that may berelated to there duction in the size of the snakes body over geological time. For this purpose, a bibliographic al review was carried out in which we sought to explore the various evolutionary and taxonomic hypotheses currently available in the literature, such as the is sue of monophyleticismof the Boidae group, considering morphological, molecular or both aspects, for a better comparison, in addition to identify whichen vironmental pressures were possibly important in the selection of animals with smaller physicalsize. The results of the bibliographic surveys how ed that there is consistente theoretical support to correlate the morphological and physiological characteristics of Boids with climate change, especial lywith the decrease in global average temperature over geological eras, which contributed to the decrease in the body of these animals. The decrease in temperature may also have been an importante selective factor for the emergence of viviparity to replace oviparity, as it contributes to greater reproductive success in snake sunder lower temperature conditions, streng the ning these considerations.